Теоретичне дослідження фізико-хімічних та кінетичних аспектів процесу фільтрації розплавів алюмінію з використанням керамічних фільтрів - Єфімова, В.Г.; Скоробагатько, Ю.П.; Смірнов, О.М.; Семенко, А.Ю.; Горюк, М.С.; Карпухін, Є.В. (Physico-technological Institute of Metals and Alloys, 2024)
It is known that aluminum and its alloys have many advantages and are one of the main structural materials. At the same time, there are numerous problems in achieving high purity of aluminum melts. In this paper it is shown that one of the main ways of refining aluminum melts is their filtration through ceramic filters. The results of previous scientific studies have shown the high efficiency of filtering aluminum melt from non-metallic inclusions through ceramic filters, which is justified by their substantial deposition on the walls of this product. However, the physico-chemical mechanism and kinetic patterns of removal of non-metallic inclusions from aluminum melt during its filtration have not been studied enough. Therefore, the goal of the research was to establish the physico-chemical regularities, as well as creating the kinetic model of the removal of non-metallic inclusions from aluminum melts. At the first stage of our research, a thermodynamic analysis of the removal of non-metallic inclusions from molten aluminum due to the action of surface and dynamic forces was conducted. The mechanism of retention of inclusions of different aggregate state and sizes by the filter surface has been considered in detail. As a result of the research, it was found that inclusions of any aggregate state (solid, liquid) up to 30 μm in size are held on the filter surface due to surface forces, liquid inclusions larger than 30 μm obey the same laws; solid inclusions larger than 30 μm are held by the gripping forces. In this case, the inclusions that have merged with each other will further act as new filter surfaces. The conducted kinetic analysis of the heterogeneous process of removal of non-metallic inclusions by the filter surface showed that the process is limited by the kinetic region and proceeds according to the first order. To confirm the reliability of the kinetic model, as well as to determine the influence of the metal pouring speed on the quality of filtration, aluminum melt was poured through a ceramic filter in laboratory conditions using filtration indicators. The conducted studies confirmed the limiting area of the heterogeneous process of filtering molten aluminum through ceramic filters, and also allowed us to establish that the efficiency of removing inclusions decreases with a decrease in the pouring speed.